INTEGRASI REMEDIASI MISKONSEPSI DALAM PEMBELAJARAN HUKUM ARCHIMEDES MENGGUNAKAN MODEL PROBLEM SOLVING DI SMP - Wiwin Wiwin; Stepanus Sahala Sitompul; Muhammad Musa Syarif Hidayatullah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to asses the effectiveness of integrated remediation of misconception with problem solving model in reducing student misconception and improving learning result related to Archimedes Law at VIII grade of SMP Negeri 3 Sungai Raya. Pre-experimental method with the design of pretest-posttest was used in this paper. Samples of study were determined by using intact group and selected by science teachers recommendation. The instrument of research included 8 questions of diagnostic test and 4 questions of learning result test. The percentage of misconcepted students in every concept and in every student dropped to 72,94% and 74,07%, respectively. Based on McNemar test, overall students experienced significant misconception with value of ?2count (131,16) > ?2table (3,84), df=1 and ? = 5%. Students learning results which were analyzed with N-Gain equation revealed a moderate increase at 0,6. The effectiveness that used to reduce the misconcepted students through DQM of 72,94% which included in high category. Keywords: Problem Solving Model, Integrated Remediation Misconception, Archimedes Law